Systemic corticosteroids for radicular and non-radicular low back pain - Chou, Roger; Pinto, Rafael Zambelli [UNESP]; Fu, Rongwei; Lowe, Robert A.; Henschke, Nicholas; Dana, Tracy (Wiley, 2016)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the benefits and harms of systemic corticosteroids compared with placebo or no systemic corticosteroid for patients with acute, subacute, or chronic radicular or non-radicular low back pain.